2012
DOI: 10.1007/s11892-012-0334-z
|View full text |Cite
|
Sign up to set email alerts
|

Current Treatment Options for Type 2 Diabetes Mellitus in Youth: Today’s Realities and Lessons from the TODAY Study

Abstract: The incidence of type 2 diabetes in children and adolescents has increased over the last 2 decades, paralleled by an increase in obesity over the same time period. Although the value of lifestyle modification in obese youth is unquestioned, scant evidence for optimal treatment of type 2 diabetes in this age group exists. Despite recent therapeutic drug trials, metformin and insulin are the only medicines currently approved by the US Food and Drug Administration for the treatment of type 2 diabetes in youth. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…To achieve this, daily oral medication (metformin) and sometimes insulin is prescribed [67**], along with daily monitoring of blood glucose, as well as other daily medications to treat various comorbidities.. Metformin, an insulin sensitizer, was shown to significantly improve glycemic control in youth with T2D [92]. Metformin and insulin are the only medications currently approved for use in youth with T2D, although a number of other medications are being considered [93*]. More controlled studies are needed for the selection and initiation of specific oral medications and insulin [67**, 94].…”
Section: Type 2 Diabetes In Children and Adolescencementioning
confidence: 99%
See 1 more Smart Citation
“…To achieve this, daily oral medication (metformin) and sometimes insulin is prescribed [67**], along with daily monitoring of blood glucose, as well as other daily medications to treat various comorbidities.. Metformin, an insulin sensitizer, was shown to significantly improve glycemic control in youth with T2D [92]. Metformin and insulin are the only medications currently approved for use in youth with T2D, although a number of other medications are being considered [93*]. More controlled studies are needed for the selection and initiation of specific oral medications and insulin [67**, 94].…”
Section: Type 2 Diabetes In Children and Adolescencementioning
confidence: 99%
“…While there is little evidence for the optimal treatment of T2D in youth [93*], it is clear that both medical and lifestyle intervention is needed, as recommended in the consensus guidelines published by the International Society of Pediatric and Adolescent Diabetes (67**). The TODAY trial is the largest randomized controlled trial available to examine treatment of T2D in youth [96**].…”
Section: Type 2 Diabetes In Children and Adolescencementioning
confidence: 99%
“…However, findings from the Treatment Options for Type 2 Diabetes in Adolescents and Youth (TODAY) study (ClinicalTrials.gov identifier: NCT00081328) suggest this treatment may be ineffective in nearly 50% of youth [7]. Early and more intensive therapy has been proposed [8].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The primary goal of type 2 DM treatment is to achieve and maintain good glycemic control, and to reduce the mortality and risk of microvascular and macrovascular complications .The current management of type 2 DM is a combination of lifestyle intervention and Metformin as initial therapy for type 2 DM, followed by other Oral Hypoglycemic Agents and Insulin. 8 Besides Biguanides (Metformin), other antidiabetic agents include Sulfonylureas, Glitinides, Thiazolidinediones or Glitazones, α-glucosidase inhibitors (Acarbose), GLP1analogues, Dipeptidyl peptidase 4 inhibitors, Amylin agonists (Pramlintide) and Sodium glucose co transport-2 inhibitors (Dapaglifozin). Therapeutic profile of Metformin has been evaluated for more than five decades and till now it is the most commonly used drug in type 2 DM.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and clinical studies have shed new light on the multiple beneficial effects of this drug, not only in the treatment of diabetes. 8,9 A number of reports have shown that antioxidants can attenuate the complications of diabetes in patients and in experimental model. 10 ACE inhibitors have been shown to attenuate the progression of cardiac and renal impairments related to diabetes and to reduce the risk of death in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%